Ammonium recovery from agro-industrial digestate using bioelectrochemical systems. (4th April 2022) - Carucci, A.; Erby, G.; Puggioni, G.; Spiga, D.; Frugoni, F.; Milia, S.
Abstract: Growing food and biomass production at the global scale has determined a corresponding increase in the demand for and use of nutrients. In this study, the possibility of recovering nitrogen from agro-industrial digestate using bioelectrochemical systems was investigated: two microbial electrolysis cells (MECs) were fed with synthetic and real digestate (2.5 gNH4 + -N L −1 ). Carbon felt and granular graphite were used as anodes in MEC-1 and MEC-2, respectively. As to synthetic wastewater, the optimal nitrogen load (NL) for MEC-1 and -2 was 1.25 and 0.75 gNH4 + -N d −1, respectively. MEC-1 showed better performance in terms of NH4 + -N removal efficiency (39 ± 2.5%) and recovery rate (up to 70 gNH4 + -N m −2 d −1 ), compared to MEC-2 (33 ± 4.7% and up to 30 gN m −2 d −1, respectively). At the optimal hydraulic retention time, lower NH4 + -N removal efficiencies and recovery rates were observed when real digestate was fed to MEC-1 (29 ± 6.6% and 60 ± 13 gNH4 + -N m −2 d −1, respectively) and MEC-2 (21 ± 7.9% and 10 ± 3.6 gNH4 + -N m −2 d −1, respectively), likely due to the higher complexity of the influent. The average energy requirements were 3.6–3.7 kWh kgNremoved −1, comparable with values previously reported in the literature and lower than conventional ammonia recovery processes. Results are promising and may reduce the need for costly and polluting processes for nitrogen synthesis. HIGHLIGHTS: Bio-electrochemical nitrogen recovery from agro-industrial digestate was achieved. Carbon felt anode allowed higher nitrogen recovery than granular graphite. Reducing the HRT had an opposite effect on nitrogen removal, depending on the anode material. Nitrogen removal rates were negatively affected by real digestate complexity. Specific energy consumption was competitive with conventional technologies for nitrogen recovery.